PHISICAL EDUCATION PROPOSPO'S CURRICULUM FOR CEAP IN AMAPÁ: (Fiep Bulletin - online, 2011)
The study was accomplished starting from the proposal curricula's of the Course of Physical education of CEAP (Center of Higher Education of Amapá), aiming at to analyze the guidelines, conceptions, contents, it forms, evaluation, profile characteristic of the course. The method of content analysis was used, proposed by Bardin(1979), to verify the tendencies declared in the prescribed pedagogic project of the course. The results appear for a proposal in that it prevails: the) the evaluation with fort focuses returned for the institutional evaluations and of the student; b) the content gone back mainly to the full licentiate's formation in physical education and c) the course conceptions in the spheres of the education, physical education and culture. Tends in view the obtained results, studies are recommended that analyze the influence of the educational performance in the execution of the proposals of curriculum, as well as studies that cross the incorporate data in the Pedagogic Project with the students' vision and of the teachers, with the purpose of identifying as these three dimensions of the formation of the professional future they are interlinked and linking in this process.
Keywords: professional formation; conception; curriculum